2020
DOI: 10.18353/crustacea.49.0_41
|View full text |Cite
|
Sign up to set email alerts
|

<i>Nerocila phaiopleura</i> (Isopoda: Cymothoidae): a new record from Ibaraki Prefecture, central Japan, with a discussion of its distribution in Japanese waters

Abstract: An ovigerous female of Nerocila phaiopleura Bleeker, 1857 was collected from the body surface of a Japanese sardine, Sardinops melanostictus (Temminck & Schlegel, 1846) (Clupeidae), caught in Hitachi Port, Ibaraki Prefecture, central Japan. This collection extends the northern distribution limit of N. phaiopleura from Kujukuri, Chiba Prefecture, to Hitachi Port, Ibaraki Prefecture. In Japan, N. phaiopleura has so far been reported from coastal waters of the western North Pacific ranging from southern Kyushu to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…3C). It is also reported that N. phaiopleura cause skin damages in a variety of fish species, including Dussumieria acuta (Ravichandran and Rameshkumar, 2014), Thunnus orientalis (Nagasawa and Shirakashi, 2017a) and Sardinops melanostictus (Nagasawa et al, 2020). In the present investigation, the damages in the body surface, buccal cavity and branchial cavity may be due to the feeding and the pressure exerted by the parasite on the host.…”
Section: Al 2005)supporting
confidence: 59%
“…3C). It is also reported that N. phaiopleura cause skin damages in a variety of fish species, including Dussumieria acuta (Ravichandran and Rameshkumar, 2014), Thunnus orientalis (Nagasawa and Shirakashi, 2017a) and Sardinops melanostictus (Nagasawa et al, 2020). In the present investigation, the damages in the body surface, buccal cavity and branchial cavity may be due to the feeding and the pressure exerted by the parasite on the host.…”
Section: Al 2005)supporting
confidence: 59%